Ethical Considerations Concerning Amnioinfusions for Treating Fetal Bilateral Renal Agenesis. Issue 1 (January 2018) - Sugarman, Jeremy; Anderson, Jean; Baschat, Ahmet A.; Herrera Beutler, Jaime; Bienstock, Jessica L.; Bunchman, Timothy E.; Desai, Niraj M.; Gates, Elena; Goldberg, Aviva; Grimm, Paul C.; Henry, Leslie Meltzer; Jelin, Eric B.; et al.
Abstract : Congenital bilateral renal agenesis has been considered a uniformly fatal condition. However, the report of using serial amnioinfusions followed by the live birth in 2012 and ongoing survival of a child with bilateral renal agenesis has generated hope, but also considerable controversy over an array of complex clinical and ethical concerns. To assess the ethical concerns associated with using serial amnioinfusions for bilateral renal agenesis, we assembled a multidisciplinary group to map the ethical issues relevant to this novel intervention. The key ethical issues identified were related to 1) potential risks and benefits, 2) clinical care compared with innovation compared with research, 3) counseling of expectant parents, 4) consent, 5) outcome measures, 6) access and justice, 7) conflicts of interest, 8) effects on clinicians, 9) effects on institutions, and 10) long-term societal implications. These ethical issues should be addressed in conjunction with systematic efforts to examine whether this intervention is safe and effective. Future work should capture the experiences of expectant parents, women who undergo serial amnioinfusions, those born with bilateral renal agenesis and their families as well as clinicians confronted with making difficult choices related to it. Abstract : Using serial amnioinfusions for the prenatal treatment of bilateral renal agenesis raises clinical and ethical issues that should be addressed when using this intervention.